Prevalence of sleep disturbance in patients with ankylosing spondylitis: a systematic review and meta-analysis - Salari, Nader; Sadeghi, Narges; Hosseinian-Far, Amin; Hasheminezhad, Razie; Khazaie, Habibolah; Shohaimi, Shamarina; Mohammadi, Masoud (BioMed Central, 2023)
Background: Ankylosing Spondylitis (AS) patients face several challenges due to the nature of the disease and its physical and psychological complications. Sleep disorders are among the most important concerns. Sleep disorders can aggravate the signs and symptoms of the disease and ultimately reduce the quality of patients’ lives. This study uses a systematic review and meta-analysis to pool the reported prevalence of sleep disorders among AS patients. Methods: To find related studies, the WoS, PubMed, ScienceDirect, Scopus, Embase, and Google Scholar databases were systematically searched without a lower time limit. Heterogeneity among the identified studies was checked using the I2 index, and the Begg and Mazumdar correlation test examined the existence of published bias. Comprehensive Meta-Analysis (v.2) software was adopted to analyze the data. Results: In the review of 18 studies with a sample size of 5,840, the overall pooled prevalence of sleep disorders among AS patients based on the random effects method was found to be 53% (95% CI: 44.9–61). The highest and lowest prevalence was in Egypt at 90% and Australia at 19.2%, respectively. Our meta-regression results show that with the increase in ‘sample size’ and ‘year of publication’, the overall prevalence of sleep disorders in patients with AS decreases (p < 0.05). Conclusion: The results of the present study indicate a high and significant prevalence of sleep disorders among AS patients. Thus, health policymakers and healthcare providers must focus on timely diagnosis and effective educational and therapeutic interventions for the prevention and proper treatment of sleep disorders in this population of patients.